Comparative performance study of LEOS and terrestrial mobile systems with reference to the DS-SSMA technique - Sivagurunathan, Balasubramaniam; Ahmed, Kazi Mohiuddin; Erke, Tapio J.; MakeHiinen, K.; Tuchinda, C.; Finnish International Development Agency (FINNIDA) Finland (Bangkok : Asian Institute of Technology, 1995)
The integration between terrestrial cellular networks and land mobile satellite based cellular networks is a very promising issue since it permits to immediately provide areas lacking in terrestrial facilities with the radio services offered by the satellite based cellular networks. This study analyze the performances of terrestrial mobile system (TMS) and land mobile satellite system (LMSS), which use direct-sequence spread-spectrum multiple access (DS-SSMA) technique with BPSK modulation, for integrating the two systems. TMS and LMSS have to be integrated in rural areas in order to provide nationwide/global coverage by the cellular networks to ensure cost effective services. In order to analyze their performance and hence integration, baseband equivalent of the asynchronous DS-SSMA system is modeled focusing on simulation aspects. Using this model, the performance of TMS and LMSS are evaluated by simulation-based approach. Since TMS can offer less expensive services compared to LMSS, the capacity (i.e., number of users) of extreme end cell in the cell cluster of TMS is maximized against BER using the technique called adaptive cell sizing. By considering a user (worst case user) moving away across the extreme end cell boundary of TMS, the BER performance of TMS for this user is obtained in order to analyze the integration. For the two systems, the channel is statistically modeled by lognormal shadowing with Rician fading. The results show that the application of adaptive cell sizing technique increases the extreme end cell capacity of TMS.
Thesis (M.Eng.) - Asian Institute of Technology, 1995
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Artificial satellites in telecommunication; Spread spectrum communications